Penanganan perempuan korban kekerasan di lembaga Kiprah Perempuan Yogyakarta - Ilham, Lailul; Casmini, Casmini (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
Woman victims of violence contrives problems on stability of psychological function which needs a quick and effective treatment in favor of being healed from trauma. This research aims to explore treatment method and its implications towards psychological aspect of women traumatized by past in KIPPER institution. It is as a descrpitive-qualitative research which uses documentation, observing, interviewing method to collect the data. This research subsequently finds that the method used is self-healing method which varies mediation-in-group technique, taking care of self, stone and flower, and body map. The method used affects towards the psychological aspects like secure feeling, having life enthusiasm, dare to speak personally in public, having chances to live normally and freedom to gather and tell their stories with others.